Forklift tray convenient to move - ZENG LIJIAO (2021)
The invention discloses a forklift tray convenient to move. The forklift tray comprises a tray transverse plate, the lower surface of the tray transverse plate is fixedly connected with the upper surface of a tray supporting plate, a storage groove is formed in the side face of the tray transverse plate, and the inner wall of the storage groove is fixedly connected with one end of a telescopic spring; and the other end of the telescopic spring is fixedly connected with one side of a push plate, the other side of the push plate is fixedly connected with one end of a movable rod, and the side face of the tray transverse plate is movably connected with one side of a fixed plate. According to the forklift tray convenient to move, by rotating a plate bolt, after the plate bolt is separated from the fixed plate, the fixed plate is taken down, the telescopic spring pops up to eject the push plate, a movable rod fixedly connected to the surface of the push plate extends out of a containing groove, a fixing bolt is sc